2012
DOI: 10.1038/ismej.2012.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patch connectivity and heterogeneity on metacommunity structure of planktonic bacteria and viruses

Abstract: Dispersal limitation is generally considered to have little influence on the spatial structure of biodiversity in microbial metacommunities. This notion derives mainly from the analysis of spatial patterns in the field, but experimental tests of dispersal limitation using natural communities are rare for prokaryotes and, to our knowledge, non-existent for viruses. We studied the effects of dispersal intensity (three levels) and patch heterogeneity (two levels) on the structure of replicate experimental metacom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 32 publications
(35 reference statements)
4
60
0
1
Order By: Relevance
“…Thus, we find that low dispersal rates in natural decomposer communities might result in apparently weak deterministic effects (low significance of environmental effect) that would have been apparent with higher dispersal rates. Supporting this idea, Lindström and Östman (2011) also found that deterministic effects in lakes only become apparent when bacterial dispersal reached intermediate rates (but see Declerck et al, 2013, where this occurs at a much lower dispersal rate). Notably, when we grouped taxa into functional groups according to their traits and performed the same community analyses, communities grouped more strongly by their local environment (data not shown), suggesting in Figure 3 Nonmetric multidimensional scaling ordinations showing simulated communities after 6 years of sorting on substrates with low lignin/N (orange, lignin/N = 20.1, 30.2, 48.6) that are low in quality and induce strong selection, or substrate with low lignin/N (blue, lignin/N = 3.9, 7.8, 12.9) that are high in quality and induce weaker selection.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, we find that low dispersal rates in natural decomposer communities might result in apparently weak deterministic effects (low significance of environmental effect) that would have been apparent with higher dispersal rates. Supporting this idea, Lindström and Östman (2011) also found that deterministic effects in lakes only become apparent when bacterial dispersal reached intermediate rates (but see Declerck et al, 2013, where this occurs at a much lower dispersal rate). Notably, when we grouped taxa into functional groups according to their traits and performed the same community analyses, communities grouped more strongly by their local environment (data not shown), suggesting in Figure 3 Nonmetric multidimensional scaling ordinations showing simulated communities after 6 years of sorting on substrates with low lignin/N (orange, lignin/N = 20.1, 30.2, 48.6) that are low in quality and induce strong selection, or substrate with low lignin/N (blue, lignin/N = 3.9, 7.8, 12.9) that are high in quality and induce weaker selection.…”
Section: Discussionmentioning
confidence: 88%
“…As it is possible that an unmeasured environmental variable (for example, iron concentration; microenvironmental factors owing to particle attachment) also correlates with both advection and community composition, future studies should address this. Mesocosm experiments 17 may also help to address the effects of small-scale exchanges of cells on community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, advection is often invoked to explain observations of microbial diversity or abundance, which do not seem attributable to environmental selection (for example, refs [13][14][15][16]. The exchange of very small volumes of water between marine microbial mesocosms has been found to greatly reduce their b-diversity (in this case, compositional differences between communities from different mesocosms) even under consistent environmental conditions 17 . This suggests that advection of even small numbers of cells could have a large homogenizing effect independent of environmental selection.…”
mentioning
confidence: 99%
“…Experimentally, much lower dispersal rates (less than 0.01%) have been shown to significantly affect metacommunity dynamics (e.g. [30]). …”
Section: (C) Diffusion and Dispersal Proceduresmentioning
confidence: 99%